Assessing the impact of computerized accounting system usage on organization performance in Tanzania: A case study on LGAs in Arusha region - Anaeli, adelisa (2024)
A dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Accounting and Finance (MSc. A & F) of Mzumbe University